2021
DOI: 10.1098/rstb.2020.0362
|View full text |Cite
|
Sign up to set email alerts
|

Land-use change and rodent-borne diseases: hazards on the shared socioeconomic pathways

Abstract: Land-use change has a direct impact on species survival and reproduction, altering their spatio-temporal distributions. It acts as a selective force that favours the abundance and diversity of reservoir hosts and affects host–pathogen dynamics and prevalence. This has led to land-use change being a significant driver of infectious diseases emergence. Here, we predict the presence of rodent taxa and map the zoonotic hazard (potential sources of harm) from rodent-borne diseases in the short and long term (2025 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 94 publications
3
13
0
1
Order By: Relevance
“…This work has found that—in the continent—certain geographic regions can present between six (Mesoamerica) and up to nine (Brazil, Bolivia, Peru and Panama) species of reservoirs. These areas are consistent with the regions, designated by Han et al ( 2015 ), as areas of high diversity and, on the other hand, areas with high rates of zoonotic risk (García-Peña et al 2021 ). These authors project risk scenarios based on anthropogenic factors such as land use, but they also consider the possible risk of exposure of the human population.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This work has found that—in the continent—certain geographic regions can present between six (Mesoamerica) and up to nine (Brazil, Bolivia, Peru and Panama) species of reservoirs. These areas are consistent with the regions, designated by Han et al ( 2015 ), as areas of high diversity and, on the other hand, areas with high rates of zoonotic risk (García-Peña et al 2021 ). These authors project risk scenarios based on anthropogenic factors such as land use, but they also consider the possible risk of exposure of the human population.…”
Section: Discussionsupporting
confidence: 86%
“…After the first outbreak in Argentina, some light was shed on the main drivers of VHFs emergence. Land use change (LUC) was considered the main driver in the emergence (Mills et al 1992 ; Charrel and de Lamberrie 2010 ), because it promotes habitat destruction and changes in the original landscape structure; which modifies community rodent structure (Suzán et al 2008 ; García-Peña et al 2021 ), then, leading to greater numbers of generalists than specialists (Murphy and Romanuk 2014 ). Generalist species have the ability to rapidly colonize more than one habitat type and achieving high population densities, thereby favoring epidemic outbreaks (Mills 2005 ; Sarute and Ross 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing awareness of the global health and economic impacts of novel zoonotic pathogen spillover, driven by the ongoing SARS-CoV-2 pandemic and previous HIV/AIDs and Spanish Influenza pandemics [1]. The number of zoonotic disease spillover events and the frequency of the emergence of novel zoonotic pathogens from rodents are predicted to increase under intensifying anthropogenic pressure driven by increased human populations, urbanisation, intensification of agriculture and climate change leading to altered rodent species assemblages [2][3][4][5]. The impact of endemic zoonoses meanwhile remains underestimated [6].…”
Section: Introductionmentioning
confidence: 99%
“…West Africa has been identified as a region at increased risk for rodent-borne zoonotic disease spillover events, the probability of these events are predicted to increase under different projected future land-use change scenarios [ 4 , 25 ]. Currently within West Africa, some rodent species are known to be involved in the transmission of multiple endemic zoonoses with large burdens on human health, these pathogens include Lassa fever, Schistosomiasis, Leptospirosis and Toxoplasmosis [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing awareness of the global health and economic impacts of novel zoonotic pathogen spillover, driven by the ongoing SARS-CoV-2 pandemic and previous HIV/AIDs and Spanish Influenza pandemics [1]. The number of zoonotic disease spillover events and the frequency of the emergence of novel zoonotic pathogens from rodents are predicted to increase under intensifying anthropogenic pressure driven by increased human populations, urbanisation, intensification of agriculture, climate change leading to altered rodent species assemblages [2][3][4][5]. The impact of endemic zoonoses meanwhile remains underestimated [6].…”
Section: Introductionmentioning
confidence: 99%